Birth weight and its associated factors among live births at Chitwan Medical College, Nepal - Chhetri, Mamta; Tripathi, Garima; Joshi, Rakshya; Koirala, Subash; Chapagain, Shakuntala; Subedi, Moni (Journal of Chitwan Medical College, 2021)
Background: Birth weight or size at birth is an essential indicator of the child’s vulnerability to the risk of childhood illnesses and diseases. Birth weight also predicts a child’s future health, growth, psychosocial development, and chances of survival. This study aimed to assess birth weight among live births in Chitwan Medical College Teaching Hospital. Methods: A Hospital-based cross-sectional study was conducted using face-to-face interviews in the Obstetrics and Gynecology Department of Chitwan Medical College Teaching Hospital. A total of 153 women giving live births were considered as a sample. The data was collected from14 August to 13 September. We used the Pearson’s Chi-square test and binary logistic regression analysis to assess the factors influencing birth weight among women giving live births in Chitwan Medical College Results: Among 153 women giving live births, birth weight of newborn among live births 119(77.8%) had normal birth weight, 31(20.3%)low birth weight, 3(2%) very low birth weight. Result shows that birth weight among live births differ significantly with [ethnicity (OR=1.94;CI(0.7-5.39)], [family income (OR=1.72(0.20-14.81)], [weeks of pregnancy (OR=2.01;(0.99-8.46)], [birth interval(OR=2.45(0.39-15.34)], [planned pregnancy (OR=1.26(0.33-4.73)], [any chronic disease(OR=1.72(0.97-4.58)], [diet in pregnancy (OR=2.11(0.20-15.07)], [ANC check-up(OR=6.75(2.44-18.64)]. Conclusions: Almost one-fourth of live births had low birth weight. Multiple arrays of factors were associated with birth weight, which must be addressed. Adequate antenatal care visits integrated with nutritional supplementation and family planning services should be a focus to reduce low birth weight among live births.